Knowledge, attitude and practices of residents toward antimicrobial usage and resistance in Gondar, Northwest Ethiopia - Haileyesus Dejene; Rediet Birhanu; Zewdu Seyoum Tarekegn (BMC, 2022)
Abstract Background Antimicrobials are essential for human and animal health. Drug resistance to an antimicrobial agent follows the introduction of a new antimicrobial agent. Evidence suggests that the public plays an important role in the risk, increase, and spread of antimicrobial resistance. This study aimed to assess the knowledge, attitudes, and practices of the Gondar City residents regarding antimicrobial use and resistance. Methods A cross-sectional study was conducted from April to July 2021 on 400 randomly selected Gondar city residents using a pretested semi-structured questionnaire. The descriptive and chi-square tests were used to analyse the data. Results The response rate was one hundred percent. Approximately 75% of respondents were men, with 32% having completed secondary school. Nearly 74% and 35% of participants were married and worked in various government jobs. Furthermore, 48%, 54%, and 50% of respondents, respectively, had moderate knowledge, a positive attitude, and good practice concerning antimicrobial use and resistance. The chi-square analysis revealed a significant (p < 0.05) disparity between knowledge and educational level, marital status, and position in the house. The respondents' attitude levels were also significantly associated (p < 0.05) with their educational level, marital status, occupation, and position in the house. Respondents' practice levels were also significantly associated (p < 0.05) with their educational level and occupation. The study also found a significant relationship between respondents' knowledge and attitude (χ2 = 215.23, p ≤ 0.01), knowledge and practice (χ2 = 147.2, p ≤ 0.01), and attitude and practice (χ2 = 116.03, p ≤ 0.01). Conclusion This study found that study participants had some misconceptions about antimicrobial use and resistance. As a result, both enforcing antimicrobial regulation and educating people about antimicrobial use are advised.